"Maximum support" = 100% BS. (9th August 2018) - Brower, Andrew V. Z.
Abstract: Bootstrap and other percentage‐based measures of nodal "support" cannot distinguish between strong support and very strong support. Clearly, if there is no upper bound to the number of potential characters, there should be no upper bound to measures of support.